TRANSFORMASI PRAKTIK PUBLIC RELATIONS DI ERA DIGITAL: STUDI DESKIPTIF TENTANG ADAPTASI TENTANG PROFESIONAL PR - Putri, Diana (Universitas 17 Agustus 1945 Surabaya, 2025)
Digital transformation has brought significant changes in Public Relations (PR) practices, demanding strategic, cultural, and technological adaptations from communications professionals. This research aims to identify and understand how PR practitioners in Indonesia adjust their communication strategies in the midst of digital changes, as well as what challenges they face in the adaptation process. Using a qualitative descriptive approach, data was collected through in-depth interviews with 15 PR professionals from various industry sectors, both private, public, and non-profit organizations, who have undergone a digitalization process in their public relations activities. The results show that PR professionals have made a significant reorientation to communication strategies, by integrating digital technologies such as social media, content marketing, and audience data analysis. These changes are also accompanied by a transformation of work culture, including the increasing need for digital competencies, work flexibility, and cross-disciplinary collaboration. However, digital adaptation also faces a number of obstacles, including digital competency gaps, limited technology infrastructure, internal organizational resistance to change, and ethical and data security challenges. This research emphasizes the importance of institutional support, ongoing training, and strategic policies that support the digital transformation of PR in an inclusive manner. This finding is expected to be a theoretical as well as practical contribution in enriching the study of communication transformation in the digital era, especially in the realm of Public Relations. Keywords: Public Relations, Digital Transformation, Professional Adaptation, Communication Strategy, Digital Competence